High Efficiency Plant Regeneration From Shoot Tip Explants Of Staurogyne Repens (Nees) Kuntze - Dogan, Muhammet (Bangladesh Journal of Botany, 2022)
A method for tissue culture of micropropagation of aquatic plant Staurogyne repens (Nees) Kuntze has been developed. Different phytohormones were investigated to optimize the growth of explants. The shoot tip explants of S. repens were placed in MS nutrient medium including BAP (0.30-1.50 mg/l) + TDZ (0.10 mg/l) + NAA (0.10 mg/l) and Kn (0.30-1.50 mg/l) + TDZ (0.10 mg/l) + NAA (0.10 mg/l). Shoot regeneration frequencies were changed as 77.77-100% and 66.66-100% in cultivation medium augmented with BAPTDZ- NAA and Kn-TDZ-NAA, respectively. In the growing media with BAP, the maximum shoot number (14.44 shoot/explant) was obtained in MS medium with 1.20 mg/l BAP + 0.10 mg/l TDZ + 0.10 mg/l NAA. In Kn applications, the highest shoot number (9.50 shoot/explant) was recorded in growing medium with 0.30 mg/l Kn + 0.10 mg/l TDZ + 0.10 mg/l NAA. The longest shoots (2.33 cm) was reached in nutrient medium with 0.90 mg/l Kn + 0.10 mg/l TDZ + 0.10 mg/l NAA. Regenerated plants rooting at 0.25 mg/l IAA have been effectively acclimated to aquarium conditions. Bangladesh J. Bot. 51(4): 697-704, 2022 (December)